2011
DOI: 10.1158/1940-6207.capr-10-0106
|View full text |Cite
|
Sign up to set email alerts
|

Melanoma Chemoprevention in Skin Reconstructs and Mouse Xenografts Using Isoselenocyanate-4

Abstract: Melanoma incidence and mortality rates continue to increase despite the use of sunscreen as well as screening programs for early surgical excision of premalignant lesions. The steady increase in melanoma incidence suggests that additional preventive approaches are needed to augment these existing strategies. One unexplored area involves targeting genes whose deregulation promotes disease development to prevent melanoma. The Akt3 signaling pathway is one key signaling cascade that plays a central role by deregu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
42
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
2

Relationship

5
4

Authors

Journals

citations
Cited by 48 publications
(42 citation statements)
references
References 45 publications
(81 reference statements)
0
42
0
Order By: Relevance
“…Epidemiologic studies have reported an inverse association between the nutritional selenium status and cancer risk 42 , suggesting that a relatively low Se status may be among the determinants of cancer risk. We have also shown selenium compounds to be effective in inhibiting tumor growth in melanoma 3134 and colon 43 xenograft models. Specifically, several synthetic alkyl and aryl selenocyanates have been evaluated for anticarcinogenicity in animal models.…”
Section: Introductionmentioning
confidence: 83%
“…Epidemiologic studies have reported an inverse association between the nutritional selenium status and cancer risk 42 , suggesting that a relatively low Se status may be among the determinants of cancer risk. We have also shown selenium compounds to be effective in inhibiting tumor growth in melanoma 3134 and colon 43 xenograft models. Specifically, several synthetic alkyl and aryl selenocyanates have been evaluated for anticarcinogenicity in animal models.…”
Section: Introductionmentioning
confidence: 83%
“…40,41 Despite some success, additional approaches are needed, which might involve preventing melanocytic lesions from developing or progressing past its earliest stages, using agents that could be added to creams, lotions or sunblocks. 42 Addition of PCP-SeCN and B(PCP)-2Se to these topical agents could be one approach to prevent melanoma. SAHA is approved by the FDA but is only marginally effective for treating solid tumors.…”
Section: Discussionmentioning
confidence: 99%
“…42,46 Low selenium levels have also been reported in the serum of patients suffering from cancers including melanoma, which could be mitigated by the selenium released from these agents. 47,48 Since incorporation of selenium in a drug can increase its efficacy for killing melanoma cells by inhibiting PI3 kinase pathway signaling, similar modifications were predicted to enhance the therapeutic potential of SAHA.…”
Section: Pcp-secn and B(pcp)-2se Inhibited Melanoma Cell Proliferatiomentioning
confidence: 99%
“…93,100,101 Mechanistically, ISC-4 has been shown to inhibit Akt3 signaling in melanomas and induce apoptotic cell death.…”
Section: Do Not Distributementioning
confidence: 99%